STRUCTURAL CHANGES IN THE RAT TESTES CAUSED BY DIAZINON ADMINISTRATION - R. TOMAN; S. HLUCHÝ; B. ŠIŠKA; M. CABAJ; J. GOLIAN; P. MASSÁNYI; N. LUKÁČ (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was to find the structural changes in the rat testis after a diazinon administration. The testis structure changes after the diazinon administration of 20 mg/kg b.w. (i.p.) and daily dose of 40 mg/l in drinking water (p.o.) were evaluated in light microscopy. 36 hours after the diazion i.p. administration, the vacuolization of the seminiferous epithelium, evacuation of germ cells into the tubule lumen, epithelium necrosis and interstitium extension were observed. After 90 days of daily oral administration, the changes in the testis were not as visible as in the acute intoxication. The germ cells released from the basal lamina and then were visible in the tubule lumen. Diazinon causes the damage of the germinal epithelium in the testes leading to the spermatogenesis failure. The infertility can then appear.